Teori Pembentukan Konsep Menurut Filsafat Objektivisme Ayn Rand - Cuk Ananta Wijaya (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2000)
The concept formation is one of the most fundamental probelms of epistemology. It includes 'How do we acquire the concepts that we have?', 'How do we come by ideas we have?' The study wants to describe and analysis Rand's theory of concept formation.Rand's theory of concept formation is based on the axiomatic assumtions-existence, identity, and consciusness. Epistemologically, the concept formation is an abstraction; metaphysically it is an intergration.Definition involved in the process of concept formation. Defining of a concept use of any other concepts. When concepts are intergrated into a wider one, the new concept includes all the characteristics of its constituent units; and when a concept is subdivided into narrower ones, its distinguishing characteristic is taken as their